Validation of an app-based portable spirometer in adolescents with asthma. (22nd March 2021) - Ring, Brian; Burbank, Allison J.; Mills, Katherine; Ivins, Sally; Dieffenderfer, James; Hernandez, Michelle L.
Abstract: Objectives: Objective measurements of asthma impairment could aid teens in recognition of changes in asthma status over time. Ready access to a conventional spirometer is not realistic outside of the clinical setting. In this proof-of-concept study, we compared the performance of the VitalFlo mobile spirometer to the nSpire KoKo® sx1000 spirometer for accuracy in measuring Forced Expiratory Volume in one second (FEV1 ) and Forced Vital Capacity (FVC) in adolescents with asthma. Methods: Two hundred forty pulmonary function measurements were collected from 48 adolescents with persistent asthma from the University of North Carolina's pediatric allergy and pulmonology subspecialty clinics. Participants performed spirometry with the nSpireKoKo® sx1000 spirometer and the VitalFlo spirometer during their clinic visits. 119 simulated FVC maneuvers were conducted on both devices to standardize measurements. Pearson correlations, Bland-Altman procedure, and two-sample comparison tests were performed to assess the relationship between the two spirometers. Results: VitalFlo measurements were significantly highly correlated with nSpireKoKo® spirometer values for FEV1, ( r 2 =0.721, [95% CI, 0.749 ± 0.120], P  < 0.001) and moderately for FVC ( r 2 = 0.617, [95% CI, 0.640 ± 0.130], P  < 0.001) measurements. There were no statistically significant differences of the mean FEV1 ( M  = 0.00764, SD = 0.364, t(59)=0.16, P  = 0.87) and FVC measurements ( M  = 0.00261, SD = 0.565, t(59)=0.036, P  = 0.97.) between the VitalFlo and nSpireKoKo® systems. Both devices demonstrated significantly high correlation when comparing the automated FVC ( r 2 = 0.997, [95% CI, 1.00 ± 0.00974], P  < 0.001) measurements. Bland-Altman plots did not demonstrate significant bias between devices for both FEV1 (0.00764 L) and FVC (0.00261 L) measurements. Conclusions: Lung function measurements from the VitalFlo mobile spirometer were comparable to a commercially-available spirometer commonly used in clinical settings. This validated app-based spirometer for home use has the potential to improve asthma self-management.